2018
DOI: 10.14419/ijet.v7i4.30.22354
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors to Science Achievement in TIMSS Malaysia: Direct Model and Indirect Model

Abstract: The purpose of this study is to examine the extent to which home context, classroom context and school context influence students' science achievement in Trends in International Mathematics and Science Study (TIMSS) 2011. This study involved a total of 5733 respondents from 180 secondary schools in Malaysia based on TIMSS 2011 data. Random sampling using two stage stratified cluster sampling technique was done in selecting the sample. This study also proposes a model containing two exogenous constructs which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A review of the literature points to several factors that contributed to the poor science performance in TIMSS among Malaysian students, such as the inferiority of science teaching (Azian, 2015), lack of home educational resources (Mohshein, 2012), lack of parental support, involvement, and engagement in learning activities at home (Ismail, Samsudin, Mohd Amin, Kamarudin, Mat Daud, & Halim, 2018), and the phenomenon where science is not adequately being valued by the students (Mokshein, 2012). Another contributing factor is that there is minimal interaction between the Malaysian science teachers and their students.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature points to several factors that contributed to the poor science performance in TIMSS among Malaysian students, such as the inferiority of science teaching (Azian, 2015), lack of home educational resources (Mohshein, 2012), lack of parental support, involvement, and engagement in learning activities at home (Ismail, Samsudin, Mohd Amin, Kamarudin, Mat Daud, & Halim, 2018), and the phenomenon where science is not adequately being valued by the students (Mokshein, 2012). Another contributing factor is that there is minimal interaction between the Malaysian science teachers and their students.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, students who will sit for TIMSS will definitely be under pressure and thus students may have negative attitude towards science and thus may have negative influence on their science achievement. As shown by Ismail et al (2017;2018) the Malaysian students who sat for TIMSS in 2011 showed a negative correlation with science achievement. However, according to Osborne et al (2003), the attitude towards science that has formed will remain and difficult to change.…”
Section: Attitude Towards Sciencementioning
confidence: 87%
“…Earlier studies involving TIMSS data mostly concentrated on separate examination of the factors influencing mathematics achievement or science achievement (Caponera & Losito, 2016;Eriksson, Helenius & Ryve, 2019;Geesa et al, 2019;Henry, Nistor, & Baltes, 2014;Ismail et al, 2018;Lay & Chandrasegaran, 2016;Mohtar et al, 2019;Mokshein, 2012;Mubarak & Abdul Razak, 2017;Saleh & Abdul Rahman, 2016). For example, Geesa et al (2019) explored the influence of home resources and attitudes towards mathematics and mathematics achievement in South Korea, Turkey, and the United States while Saleh and Abdul Rahman (2016) examined the effects of gender and school type on students' achievement in algebra.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Geesa et al (2019) explored the influence of home resources and attitudes towards mathematics and mathematics achievement in South Korea, Turkey, and the United States while Saleh and Abdul Rahman (2016) examined the effects of gender and school type on students' achievement in algebra. Contributing factors of science achievement using TIMSS data were studied by Mokshein (2012), Lay and Chandrasegaran (2016), Mubarak andAbdul Razak (2017), andIsmail et al (2018). Both Ismail et al (2018), and Lay and Chandrasegaran (2016) did their studies on the determining factors of science achievement among Malaysian eighth graders using TIMSS 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation